MANAGEMENT OF ALLERGIC STOMATITIS CAUSED BY CHICKEN AND EGG : TATALAKSANA STOMATITIS ALERGIKA YANG DISEBABKAN ALERGI AYAM DAN TELUR - Ganesha, Raziv (Interdental Jurnal Kedokteran Gigi (IJKG), 2022)
Introduction: Aller gic stomatitis is a hypersensitivity reaction caused by an allergen such as medicines, foods, dental materials. Chicken and egg are one of the common food we usually consumed. Chicken contains low amount of protein and fat, while egg contains nutrient and easy to process. Although allergic reactions in poultry products are commonly found in eggs and feathers, chicken is often as a cause of the allergic reaction. Case: 28-year-old male patient complained an ulcer in his mouth. It shows past 3 days on his upper lips then it shows on his left cheek. Case Treatment: Diagnosis made by anamnesis, clinical examination and supporting examination such as complete blood count, total IgE, and Skin Prick Test. The patient was prescribed by topical anti-inflammatory 2 times daily and after Skin Prick Test was done the patient was given methylprednisolone 3 times daily for 7 days, patient was treated in 3 visits. Discussion: A Food allergic usually involved type 1 and 4 hypersensitivity reaction, or both. Skin Prick Test is one of the skin test that commonly used by clinicians to prove the presence of specific IgE bound to skin mastocyte cells. Treatment for this case beside of medication was advised to avoid food that cause the allergic reaction. Conclusion: Management of this case can be successful if clinician understand the clinical manifestation of hypersensitivity reaction to food and can made the right diagnosis to provide proper treatment. Furthermore requires patient cooperation to follow the prescribed care instruction.